P095 PSYCHOLOGICAL DISTRESS IN PATIENTS WITH CROHN'S DISEASE: A CROSS-SECTIONAL STUDY USING THE BRIEF SYMPTOM INVENTORY INSTRUMENT. (18th January 2018) - Odes, Shmuel; Slonim-Nevo, Vered; Sergienko, Ruslan; Friger, Michael; Schwartz, Doron; Greenberg, Dan; Sarid, Orly
Abstract: Background: Crohn's disease (CD) patients all experience psychological distress, but its characteristics are incompletely understood. We report an in-depth cross-sectional study in 297 patients. Methods: The Brief Symptom Inventory (BSI, Derogatis 1983) measures psychological distress: 59 items assess depression, somatization, obsession-compulsive, interpersonal sensitivity, anxiety, hostility, phobic anxiety, paranoid ideation and psychoticism. BSI summary scores are: General Severity Index (GSI, mean of category scores, range 0–4), Positive Symptom Total (PST, sum of recorded symptoms) and Positive Symptom Distress Index (PSDI, summated item values divided by PST); higher scores imply more distress. Patients completed demographics, Patient-Harvey-Bradshaw Index (P-HBI), BSI, Family Assessment Device (FAD, measures family functioning) and Multidimensional Scale of Perceived Social Support (MSPSS, measures social support). Results: GSI scores were similarly elevated in men 1.0 ± 8.7 and women .0 ± 8.8, but significantly higher in single 1.2±.8 vs coupled .9±.8, smokers 1.3±.8 vs non-smokers .9±.8 and non-working 1.2±.9 vs working .9±.7. PST scores were: men 25.8 ± 15.2 vs women 26.4 ± 13.7 (ns), single 29.6 ± 14.0 vs coupled 23.1 ± 14.0, smokers 30.3 ± 14.0 vs non-smokers 25.0 ± 14.4 and non-working 29.3 ± 14.6 vs working 24.4 ± 18.8. PSDI scores were: men 1.8 ± 1.7 vs women 1.8 ± 1.7 (ns), single 1.9±.6 vs coupled 1.7±.6, smokers 2.0±.6 vs non-smokers 1.7±.6, and non-working 1.9±.7 vs working 1.7±.6. GSI, PST and PSDI scores correlated significantly with age, economic status, P-HBI, FAD and MSPSS (Table 1). Multivariate regression analysis identified age, economic status, FAD, MSPSS, P-HBI as predictors of distress (Table 2). Notably, gender did not predict distress. Conclusion: Psychological distress is increased in CD and predicted by age, economic status, family relationship, social support and disease activity. Caregivers should incorporate these findings in patient management.